Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil - Palacios-Vargas, José G.; Ferreira, Aila Soares; Zeppelini, Douglas (Zootaxa, 2018)
A new diagnosis of Denisiella is provided, based on the revision of most descriptions, including three new species from Brazil. New Brazilian taxa share the presence of 6 + 6 eyes, 4 + 4 serrate spine-like on tibiotarsi III and the polycarinate setae on tibiotarsi II but differ from each other by the shape and size of the sensilla of the tibiotarsi I. Denisiella rhizophorae sp. nov. has the combination of sensilla on tibiotarsi I of rhagidial type and C2 blunt on antennal segment III. Only D. betschi sp. nov. has barbulate spines on head and D. caatingae sp. nov. is the only which males present nasal organ. They are illustrated with drawings and scanning electron microscope photographs. Three different shapes of sensilla in the tibiotarsi I were observed and were compared with other species.